Analisis Peningkatan Produksi Pada Sumur Minyak Dengan Metode Partial Water Shut Off Dalam Meningkatkan Rasio Keberhasilan Partial Water Shut Off Pada Lapangan Hawa - Fitrianti Fitrianti (Universitas Islam Riau (UIR) Press, 2017)
From year to year the number of oil production will be reduced and the amount of water production will grow, so will cause problems in managing the water. Some of the problems that arise are limitations in the surface water treatment systems, the availability of water treatment chemicals, and declining well productivity. Doing some work over to lower the value of water production and increase the value of oil production, one of which is the partial water shut off. On the hawa field, some job well done partial water shut off. The results of such work nothing works and nothing failed. Analysis performed on the job partial water shut off with the observation of the historycompletion and the processing of data and calculation of the value of production history OOIP to get the value of remaining reserves. After analysis, it was found some causes of work partial water shut off the well would be successful if it fulfills several criteria such as: the value of remaining reserves are still large enough, she had never done work partial water shut off in the layer and selecting the type of isolation right tool. While the cause of such failures is that the well had done work partial water shut off the same perforation interval. The criteria are very important and necessary in deciding the work partial water shut off the a better well done or not.